Clinical efficacy studies of the vaccine against feline panleukopenia, calicivirus infection and viral rhinotracheitis Carnifel PCH in kittens - T. S. Galkina; A. A. Komarova; A. M. Kiselev (Ветеринария сегодня)
Viral infections in cats can cause serious diseases and even death. Vaccines protect animals from diseases by inducing antibody production and cellular immune response. Primary and booster vaccinations are performed in accordance with the recommendations for the use of vaccines prescribed by the manufactures depending on the minimum duration of immunity. In case of feline panleukopenia, antibody titers correlate with the protection against infection, as for feline calicivirus infection and feline rhinotracheitis, there is no such correlation or it is less clear. Vaccination of cats against these diseases has been performed in the Russian Federation for many years, nevertheless, the feline panleukopenia virus (FPV), feline calicivirus (FCV) and feline herpesvirus (FHV) are still the main common cause of morbidity and mortality among cats. Virus-carrying cats play an important role in the transmission of respiratory viruses such as FHV and FCV in the feline population, and the long-term persistence of FPV in the body, stability in the environmental conditions and resistance to disinfecting agents can be a potential cause of the infection in susceptible kittens. Due to variety of antigenically different FCV strains, the use of the vaccines containing two or more viral strains may induce a broader heterologous protection. The purpose of this work was to evaluate the effectiveness of the vaccine against feline panleukopenia, feline calicivirus infection and feline viral rhinotracheitis developed at the Federal Center for Animal Health (Vladimir) subordinate to the Rosselkhoznadzor, containing 2 heterologous FCV strains (Pers strain genotype I and Fauna strain genotype II), FPV Sheba strain and FHV Lavr strain. The product was developed and tested for its quality in accordance with the requirements of the Russian Federation law. Clinical studies were conducted using 8–12 week-old kittens from different litters born from seronegative, non-vaccinated cats and kept in the household, in a veterinary hospital and animal shelters. The product has successfully passed comprehensive quality control and is registered in the territory of the Russian Federation.